-23(-2)=x

Simple and best practice solution for -23(-2)=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -23(-2)=x equation:


Simplifying
-23(-2) = x

Multiply -23 * -2
46 = x

Solving
46 = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
46 + -1x = x + -1x

Combine like terms: x + -1x = 0
46 + -1x = 0

Add '-46' to each side of the equation.
46 + -46 + -1x = 0 + -46

Combine like terms: 46 + -46 = 0
0 + -1x = 0 + -46
-1x = 0 + -46

Combine like terms: 0 + -46 = -46
-1x = -46

Divide each side by '-1'.
x = 46

Simplifying
x = 46

See similar equations:

| 5x+4(x-13)=5(x-8) | | V(2v-1)=0 | | 4y(2y-3x)-2x(x-3y)= | | (-9)[3+3]-12= | | 8n+16.2=1.825 | | 22.5+7.5= | | 3/2(x-5)=/6 | | x(3x-5)=(3x+6)(x-3) | | 6(x-8)=12(x+4) | | 3n+5n+2+n= | | (4q+9)(4q+9)=0 | | 4(x+3)=2x+10+2x | | 46/63-5/7 | | 57+57+123+x=360 | | 5+3(y-4)=5(y+3)-y | | -9+6-12= | | 5+7g=54 | | 12x+17x-6+5=-5x+5-6 | | 63=9(2-w) | | 6-4(5p+9)+3(2+p)=-18 | | 3t-18=4(-3-3/4) | | -6x+5(1)=1 | | 6n=64 | | 4.6x-14.6=5.4 | | 2(n+n+1)=(n+2)-36 | | 3/5x-2=1/5 | | 10y(y+2)+3x=5(3-x) | | 4y-2(x-y)= | | 5x-3x+16=-x+8 | | 9w-8=64 | | 5.50-3.75= | | 8+2x+3-x=2+1 |

Equations solver categories